The Effects of Working Memory and Linguistic Intelligence as a Cognitive Aspect of Individual Differences on Foreign Language Learning - Elmechta , Lamia (Journal of Social Sciences and Humanities, 2020)
Individual differences are quite apparent in a language instruction. Some learners find it rather easy to acquire very complex foreign language rules (with regard to grammar, vocabulary and phonetics), others struggle with even the simplest rules. Individual differences (ID) research is thoroughly dealt with in the field of second language acquisition. A number of aspects are believed to affect the acquisition of a second/foreign language. These factors are: cognitive, affective, social, to name but a few. This paper purports to scrutinize the influence of the cognitive aspect of individual differences on foreign language learning. Two cognitive abilities were highlighted, viz. working memory and linguistic intelligence, and their relationship with foreign language achievement was investigated. A measure of each of these abilities was administered to a sample of sixty first year freshman students learning English as a Foreign Language at the department of Letters and English, University of Frères Mentouri Constantine 1. Working memory measure contained four subtest that assess working memory capacity in the foreign language; while linguistic intelligence test comprised five subtests that assess both inductive and deductive reasoning skills. Correlations were made between the obtained scores in these measures and the students’ language learning achievement. The results revealed significant associations between this latter and the two cognitive abilities: working memory and foreign language learning achievement (.29) and linguistic intelligence and foreign language learning achievement (.28). The study cognition adds evidence to the importance of cognition in foreign language learning and would recommend the implementation of a cognitive linguistic test as a basis for selection for Baccalaureate holders who opt to learn English as a foreign language at university to ensure success